2018
DOI: 10.1186/s12871-018-0635-0
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory variation in peripheral arterial blood flow peak velocity to predict fluid responsiveness in mechanically ventilated patients: a systematic review and meta-analysis

Abstract: BackgroundFluid overloading is detrimental to organ function and results in a poor prognosis. It is necessary to evaluate fluid responsiveness before fluid loading. We performed a systematic meta-analysis to evaluate the diagnostic value of the respiratory variation in peripheral arterial blood flow peak velocity (△Vpeak PA) in predicting fluid responsiveness in mechanically ventilated patients.MethodsPubMed, Embase and The Cochrane Library databases were searched for studies that used △Vpeak PA to predict flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…Several meta-analyses have evaluated the operative performance of these predictors in different clinical settings [9][10][11][12][13][14][15][16][17][18][19][20]. Differently from this current metanalysis, patients included received Vt from 4.9 to 12 ml kg −1 [9,10,17] and evaluated other types of populations [14,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several meta-analyses have evaluated the operative performance of these predictors in different clinical settings [9][10][11][12][13][14][15][16][17][18][19][20]. Differently from this current metanalysis, patients included received Vt from 4.9 to 12 ml kg −1 [9,10,17] and evaluated other types of populations [14,18].…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses evaluating the operative performance of fluid responsiveness predictors in different clinical settings have led to variable results [9][10][11][12][13][14][15][16][17][18][19][20]. These meta-analyses, however, did not evaluate specific subgroups, and there are no meta-regressions assessing the reliability of methods to evaluate fluid responsiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, noninvasive dynamic indices that calculate variation of peak velocity of the artery during several respiratory cycles measured by ultrasound have become an alternative quick volume assessment method [20, 21]. However, vessels in pediatric patients are thinner and more variable than adults.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, all studies to date comparing carotid DVpeak against an objective measure of fluid responsiveness have used expert sonologists. 15,[18][19][20] Our study demonstrates that novice physician sonologists were unable to accurately predict fluid responsiveness using POCUS measurement of carotid DVpeak (AUROC ¼ 0.61). The carotid DVpeak cutoff of 8% derived by maximizing the sensitivity and specificity of our observed data was unable to distinguish between fluid responders and non-responders.…”
Section: Discussionmentioning
confidence: 78%
“…[15][16][17][18] A 2018 meta-analysis that included mechanically ventilated patients with a variety of diagnoses and in several clinical settings reported that carotid DVpeak is able to predict fluid responsiveness with a pooled area under the receiver operating curve (AUROC) of 0.92. 19 A study of spontaneously breathing patients that compared POCUS measured aortic velocity time integral to carotid POCUS showed that carotid DVpeak performed well predicting fluid responsiveness (AUROC ¼ 0.81). Test characteristics of carotid DVpeak among nonintubated patients were diminished compared to mechanically ventilated patients, suggesting that heart-lung interactions may make carotid DVpeak less reliable when used with spontaneously breathing patients.…”
Section: Introductionmentioning
confidence: 99%